317 Effect of the Whole Cottonseed with Pre-treatment on the Digestibility, Productivity, and Milk Fat Profile of Dairy Cattle. (8th October 2021) - Sun, Xiaoge; Su, Yitong; Hao, YangYi; Liu, Gaokun; Gong, Yue; Wang, Yajing; Cao, Zhijun; Wang, Wei; Li, Shengli
Abstract: To improve the efficiency of whole cottonseed (WCS) on dairy cattle, crush and alkali treatment were combined (Table 1) in this study. The gastrointestinal tract digestibility of WCS were measured by in situ ruminal incubation and in vitro fermentation, respectively. Finally, animal feeding experiment was conducted to evaluate the effect of processed WCS on dairy cattle. A total of 30 Holstein dairy cows with similar physiological status were allocated to three groups (CON, Group I, and Group II). Ration for the CON group was a basic ration with no WCS, ration with about 8% non-processed WCS was for Group I (DM basis), while the Group II was provided by the ration added with 8% Crush-Alkali (4% mixed alkali solids with NaOH/CaO ratio at 1:1) treated WCS. Results of the in situ and in vitro experiments showed that, compared with non-treated WCS, Crushing-Alkali treatment groups significantly improved WCS ruminal effective degradation rate of dry matter (DM), crude protein (CP), ether extract (EE), and neutral detergent fiber (NDF) (P < 0.05). Furthermore, Crush-Alkali (4% mixed alkali solids with NaOH/CaO ratio at 1:1) was the most beneficial to improve WCS gastrointestinal degradation of DM, CP and NDF, as well as enhance WCS rumen-bypass of EE. With the lowest free gossypol content (P< 0.05). Results of animal feeding experiment showed that DMI, 4% fat corrected milk production (4% FCM), milk protein, milk fat, and content of short-chain saturated fatty acids in milk in Group II significantly increased (P < 0.05) compared with CON group. DMI, ω-6 polyunsaturated fatty acids (PUFA) in milk, and the ratio of ω-6 to ω-3 PUFA were significantly higher in Group II than that in Group I (P < 0.05). Additionally, free gossypol concentration in serum and milk, as well as parameters reflecting liver function were not notably different among the three groups (P > 0.05).